Eco-Friendly Sidewalk Lights - Abdullah, Noor Dyna Qurratuainy; Abdul Rahim, Nurul Awatif (2016)
Eco-friendly Sidewalk Lights is designed to save the energy of electricity of light. This project consists of PIR motion sensor and LDR sensor. The project will operate when there is a motion that detect by PIR motion sensor. This sensor will detect movement through picking up infrared waves. When someone emits infrared waves, the detector is able to detect the wave and it react to switch ON the light automatically. Besides, LDR sensor is use to detect the day and night. LDR sensor operate functionally at night only and the light will turn ON. Furthermore, the microcontroller of PIC16F877A as a brain to control circuit so that the project can functionally operates. This project is design by using Proteus 7 software.